English Medium Instruction in Algeria: Investigation of Teachers’ Perceptions and Attitudes at Souk-Ahras University The Case of Teachers of Other Disciplines at Souk-Ahras University - Lyna MAHREZ (My University, 2024)
Abstract As globalization continues to shape the educational landscape, the adoption of English as a language of instruction has become a major priority for policymakers seeking to strengthen global integration and competitiveness. This study examines the attitudes and performance of professors at Muhammad Sharif Musadia University regarding the implementation of English as a medium of instruction in various academic fields. Adopting a descriptive and exploratory research design, data was collected through non-participant observation and a structured questionnaire distributed to 30 faculty from various disciplines including biology, finance, science and technology. The results reveal a range of attitudes towards English as a language of instruction among teachers, with varying degrees of enthusiasm and hesitation across different disciplines. While teachers in fields such as veterinary science and sports display a positive attitude towards English as a medium of instruction, their counterparts in other disciplines express reservations. Among the main challenges identified by teachers are the low level of linguistic competence of students, the influence of the mother tongue (Arabic) on learning, the need for training and professional development of teachers, the lack of appropriate teaching materials and resource constraints. --------------------- ملخص مع استمرار دور العولمة في تشكيل مشهد التعليم، أصبح اعتماد اللغة الإنجليزية كوسيلة للتعليم محوراً أساسياً لصانعي السياسات الذين يسعون لتعزيز التكامل العالمي والتنافسية. تبحث هذه الدراسة في مواقف واداء الأساتذة في جامعة محمد شريف مساعدية تجاه تنفيذ اللغة الإنجليزية كوسيلة للتعليم عبر مختلف المجالات الأكاديمية. باعتماد تصميم بحثي وصفي واستكشافي، تم جمع البيانات من خلال الملاحظة غير المشاركة واستبيان منظم تم توزيعه على 30 أستاذًا من تخصصات متنوعة بما في ذلك البيولوجيا والمالية والعلوم والتكنولوجيا. تكشف النتائج عن طيف من المواقف تجاه اللغة الإنجليزية كوسيلة للتعليم بين الأساتذة، مع تباين درجات الحماس والتردد عبر التخصصات المختلفة. بينما يظهر الأساتذة في مجالات مثل العلوم البيطرية والرياضة مواقف إيجابية تجاه اللغة الإنجليزية كوسيلة للتعليم، يعبر نظراؤهم في تخصصات أخرى عن تحفظاتهم. من بين التحديات الرئيسية التي حددها الأساتذة، تشمل انخفاض كفاءة اللغة لدى الطلاب، تأثير اللغة الأم (العربية) على التعلم، الحاجة إلى تدريب الأساتذة والتطوير المهني، نقص المواد التعليمية المناسبة، وقيود الموارد -------------------- résumé Alors que la mondialisation continue de façonner le paysage éducatif, l’adoption de l’anglais comme langue d’enseignement est devenue une priorité majeure pour les décideurs politiques cherchant à renforcer l’intégration et la compétitivité mondiales. Cette étude examine les attitudes et les performances des professeurs de l'Université Muhammad Sharif Musadia concernant la mise en œuvre de l'anglais comme langue d'enseignement dans divers domaines académiques. En adoptant une conception de recherche descriptive et exploratoire, les données ont été collectées par le biais d'observations non participantes et d'un questionnaire structuré distribué à 30 professeurs de diverses disciplines, notamment la biologie, la finance, les sciences et la technologie. Les résultats révèlent un éventail d’attitudes à l’égard de l’anglais comme langue d’enseignement parmi les professeurs, avec différents degrés d’enthousiasme et d’hésitation selon les différentes disciplines. Alors que les professeurs de domaines tels que les sciences vétérinaires et les sports affichent une attitude positive à l'égard de l'anglais comme langue d'enseignement, leurs homologues d'autres disciplines expriment des réserves. Parmi les principaux défis identifiés par les professeurs figurent le faible niveau de compétence linguistique des étudiants, l'influence de la langue maternelle (arabe) sur l'apprentissage, le besoin de formation et de développement professionnel des professeurs, le manque de matériel pédagogique approprié et les contraintes de ressources.